Use of Optical Coherence Tomography in Dentistry - Omer Sefvan Janjua; Waqar Jeelani; Muhammad Ikram Khan; Sana Mehmood Qureshi; Muhammad Saad Shaikh; Muhammad Sohail Zafar; Zohaib Khurshid (International Journal of Dentistry)
Optical coherence tomography (OCT) is an optics-based imaging technique, which may be called an “optical biopsy.” It can be used to acquire structural information about a tissue at a resolution comparable to histopathology. OCT is based on the principle of low-coherence interferometry where near-infrared (NIR) light is shown on a tissue sample and then cross-sectional images are obtained based on backscattered light and echo time delay. Two main types of OCT are characterized as time-domain OCT (TD-OCT) and Fourier-domain OCT (FD-OCT). The applications of OCT in dentistry can be broadly divided into two groups, i.e., assessment of pathologies and assessment of surfaces and interfaces. Lately, OCT has made its transition from experimental laboratories to mainstream clinical applications. Starting from the short-term training courses, clinicians working in specialities like oral pathology, oral medicine, and oral implantology may find it a useful tool for their practices. It is now clear that OCT will be considered a gold standard diagnostic tool for the detection and characterization of several conditions and lesions of the orofacial region. However, the next challenge will be to incorporate it into the undergraduate and postgraduate curriculum and train dental healthcare staff in the use of these devices.